Catheter ablation as first-line treatment for paroxysmal atrial fibrillation: a systematic review and meta-analysis. Issue 20 (14th July 2021) - Imberti, Jacopo F; Ding, Wern Yew; Kotalczyk, Agnieszka; Zhang, Juqian; Boriani, Giuseppe; Lip, Gregory; Andrade, Jason; Gupta, Dhiraj
Abstract : Objective: To assess the efficacy and safety of catheter ablation (CA) compared with antiarrhythmic drugs (AADs) as first-line treatment for symptomatic paroxysmal atrial fibrillation (AF). Methods: Systematic review and meta-analysis of randomised controlled trials identified using MEDLINE, Cochrane Library and Embase published between 01/01/2000 and 19/03/2021. The primary efficacy endpoint was the first documented recurrence of atrial arrhythmias following the blanking period. The primary safety endpoint was a composite of all serious adverse events (SAEs). Results: From 441 records, 6 studies met the inclusion criteria. 609 patients received CA, while 603 received AAD therapy. 212/609 patients in the CA group had a recurrence of atrial arrhythmias as compared with 318/603 in the AADs group resulting in a 36% relative risk reduction (risk ratio: 0.64, 95% CI 0.51 to 0.80, p<0.01). The risk of all SAEs was not statistically different between CA and AAD (0.87, 0.58 to 1.30, p=0.49); 107/609 SAE in the CA group vs 126/603 in the AAD group. Both recurrence of symptomatic atrial arrhythmias (109/505 vs 186/504) and healthcare utilisation (126/397 vs 185/394) were significantly lower in the CA group (0.53, 0.35 to 0.79 and 0.65, 0.48 to 0.89, respectively). There was a 79% reduction in the crossover rate during follow-up among patients randomised to CA compared with AAD (0.21, 0.13 to 0.32, p<0.01). Conclusions: First-line treatment with CA is superior to AAD therapy in patients with symptomatic paroxysmal AF, as it significantly reduces the recurrence of any atrial arrhythmias and symptomatic atrial arrhythmias, and healthcare resource utilisation with comparable safety profile.